KELIMPAHAN KUPU-KUPU (LEPIDOPTERA) DI KAWASAN CAGAR ALAM GUNUNG AMBANG SULAWESI UTARA - Koneri, Roni (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2016)
Gunung Ambang Nature Reserve is one of the preserved areas which serve to protect the flora and fauna that live in it. This study aimed to analyze the abundance of butterflies (Lepidoptera) on various types of habitat in the area of the Gunung Ambang Nature Reserve, North Sulawesi. Sampling of habitat include primary forest, secondary forest, plantation and scrub. Sampling used a sweeping technique that follows the line transect which applied at random along the 1000 meters in each habitat type. The result obtained 5 families of insect, that Nymphalidae, Papilionidae, Pieridae, Riodinidae, and Satyridae, including 37 species and 560 individuals. The most Family found are Nymphalidae (72.50%), while the majority of species is Lohara dexaminus (24.64). The highest abundance of butterflies found in scrub habitat and the lowest on the plantation. Results of this research are expected to be the data base about the abundance of butterflies in North Sulawesi.